THE EFFECT OF ALKALI ACTIVATOR MOLARITY ON THE MECHANICAL PERFORMANCE OF GEOPOLYMER PAVING BLOCKS BASED ON WASTE GLASS POWDER AND FLY ASH - Adji Putra Abriantoro; Manlian Ronald Adventus Simanjuntak (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
The effect of concentration of sodium hydroxide (NaOH) on physical and mechanical properties of geopolymer paving blocks consist of fly ash type F and glass powder. A quantitative experimental method was used both the NaOH molarity (1M, 2M, 4M, 6M, 8M and 10M) was studied and the compressive strength, flexure strength and water absorption were taken as key parameters. The ratio of alkali activator to binder was 0.35, and the ratio of Sodium Silicate/NaOH was 1.5. The best performance at 4M molarity yielded compressive strength of 35.60 MPa and flexural strength of 4.29 MPa, due to optimal geopolymerization and denser microstructure. The mechanical performance of the geopolymer paving blocks was compromised at NaOH molarities higher than 4M due to the emergence of a micropore, which increased the porosity and water absorption from 6.55% at 1M to 9.14% at 10M. These results confirm that increasing NaOH molarity is vital for producing geopolymer paving block with high performance. Hence, this study contributes to sustainable construction by using waste products of industries for producing construction and building materials.